Integrating Islamic Values into ESP Reading Material (NOBEL: Journal of Literature and Language Teaching, 2019)
This present research is aiming at developing suitable instructional reading material for the students of Islamic Education Department. The procedure employed in this study was R&D model proposed by Dick and Carey, namely, need analysis, developing reading materials, expert validation, revising the materials, trying out the materials, and revising the materials. The result shows that reading materials must be developed by incorporating major content subject, namely Islamic studies, list of vocabulary, grammar review, and reading comprehension exercises. Furthermore, after being tried-out, it shows the applicability of the developed materials in helping the students to accomplish the mastery of reading skills and improve their learning motivation. In spite of the strength of the material developed, it is still tried-out in the small scale; therefore, the materials were still possible to be revised.